Perancangan Sistem Webgis untuk Visualisasi Data Wilayah,Potensi Daerah, dan Infrastruktur Strategis di Bappeda Sulawesi Tenggara sebagai Upaya Mendukung Pengabdian kepada Masyarakat - Maulana, Muhammad fauzan; Irwan Syahib, Muhammad; Apriliyanti, Nurul Aulia; Indri, Indri; wibowo, Asa Hari; Yamin, Muhammad (FAKULTAS TEKNIK UMKENDARI, 2025)
WebGIS (Web Geographic Information System) is a web-based geographic information system that allows users to access, display, and analyze spatial data interactively over the internet. This research aims to design and implement a WebGIS system that presents information on administrative areas, regional potential, and strategic infrastructure in Southeast Sulawesi Province. The system was developed using the CodeIgniter 4 framework as the backend, along with Leaflet.js and GeoJSON for dynamic map visualization. The data used in this system includes district/city boundaries, capital city names, population, area, density, and spatial information related to resource potential and infrastructure facilities. Key features developed include region selection based on district/city name, satellite and road basemap displays, click coordinate determination, distance measurement, and area radius determination. The system also features a search panel, layer controls, and GeoJSON-based data visualization that can be customized to suit the needs of user agencies. Implementation results indicate that this WebGIS system is capable of displaying spatial information effectively, accurately, and interactively, and can be used as a supporting tool in the regional development planning process by agencies such as the Regional Development Planning Agency (BAPPEDA). The system can also be further developed to include real-time data integration, a user login system, and advanced spatial analysis. Thus, this WebGIS development is expected to improve the efficiency and effectiveness of regional data management in Southeast Sulawesi.